Effect of Work Fatigue and Workload on Organizational Commitment on Operators at PT Tunas Baru Lampung Tbk-Banyuasin - Reka Damayanti; Dina Mellita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of Work Fatigue and Workload on Organizational Commitment at PT. Tunas Baru Lampung, Tbk-Banyuasin. The sample in this study was 70 respondents. This type of research uses a quantitative approach and uses a Likert scale. The analysis used is multiple linear regression, and hypothesis testing using T-test and F test which is processed using SPSS V.25 program and produces the regression equation Y = 32.694 – 0.127X1+0.155X2. The result of this research is that work fatigue has no significant effect on organizational commitment while the workload has a significant effect on organizational commitment at PT. Tunas Baru Lampung, Tbk-Banyuasin. This can be seen from the T-test, namely T count 1.893 with a significant level of 0.000 <0.05 T count > T table (1.893> 1.667.